Spy school revolution - Gibbs, Stuart, 1969- (Gibbs, Stuart, 1969- Spy school novel., 2020)
With SPYDER apparently defeated, thirteen-year-old Benjamin Ripley is hoping for some peace at spy school, but when the CIA conference room next to where Ben and Alexander are trying to explain everything to Ben's parents (no easy task) is blown up, suspicion falls on fellow trainee (and secret crush) Erica.